Extractive Spectrophotometric Method for Determination of Pioglitazone Hydrochloride in Raw Material and Tablets Using Ion-Pair Formation - Massoud Amanlou; Mohadeseh Zarei-Ghobadi; Mohammad Kazem Rofouei; Shahrooz Saremi; Abbas Kebriaeezadeh (E-Journal of Chemistry)
A simple, rapid and extractive spectrophotometric method was developed for the determination of pioglitazone hydrochloride in pure and pharmaceutical formulations. This method is based on the formation of yellow ion-pair complex between the basic nitrogen of the drug and bromocresol green (BCG) in phthalate buffer of pH 2.4. The formed complexes were extracted with chloroform and measured at 419 nm. The analytical parameters and their effects on the proposed systems are investigated. Beer’s law was obeyed in the range 2.5-14 μg/mL with correlation coefficient ≥ 0.995. The proposed method has been applied successfully for the determination of drug in commercial tablets dosage forms. No significant interference was observed from the excipients commonly used as pharmaceutical aids with the assay procedure. The validity of the proposed method was established by parallel determination against HPLC method and there was no significant difference between these two methods.